(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Faced with the complex relationship between leaf reflectance and physiological aspects of the plant on days and at different times of the day, the research was developed to ascertain and measure the influence of day and period of the day on leaf reflectance of eucalyptus trees. The experiment was carried out in a clonal eucalyptus stand, spontaneous Eucalyptus grandis hybrid with centroid at 18º 12 ’12,19’S and 43º 34’ 20,28’’W. In each of the five sample trees randomly selected, four leaves were sampled at each cardinal point. All selected leaves were evaluated on days 7, 8, 9 and 10 of December 2013, in two periods of the day: between 8 and 9 hours and between 15 and 16 hours. The leaf reflectance was measured using a mini-spectrometer with subsequent smoothing and the analysis of principal components and subsequent analysis of dendrogram cluster were performed. In general, the average leaf reflectance on the second day was the lowest and the third day average was higher. Leaf reflectance was lower in the morning than in the afternoon. The day and period of the day of reading were randomly influenced by eucalypt leaf reflectance. The leaf reflectance of eucalyptus can change in a short time, even in the same day, which indicates the importance of the standardization in the collection schedule for future studies.